2017
DOI: 10.1002/pon.4334
|View full text |Cite
|
Sign up to set email alerts
|

Sharing information about cancer with one's family is associated with improved quality of life

Abstract: Encouraging patients to share information about their experience of cancer may help to improve their quality of life. Attachment security seems to promote social sharing. Psychological assessments of cancer patients should cover both ability to share information about one's cancer with family and attachment security.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…However, a previous study showed that bladder cancer diagnosis did not significantly affect the patients’ levels of anxiety and depression [28], thus suggesting that QoL may not be significantly influenced by these issues in bladder cancer patients. Also, little attention has been paid to the psychosocial issues of the patients and the importance of these in relation to a person’s QoL, which ultimately could explain the reported levels of QoL in the different domains [29]. These issues are described in the literature in the general cancer population [30–33].…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study showed that bladder cancer diagnosis did not significantly affect the patients’ levels of anxiety and depression [28], thus suggesting that QoL may not be significantly influenced by these issues in bladder cancer patients. Also, little attention has been paid to the psychosocial issues of the patients and the importance of these in relation to a person’s QoL, which ultimately could explain the reported levels of QoL in the different domains [29]. These issues are described in the literature in the general cancer population [30–33].…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of the diagnosis is a factor that is worth investigating in future research, as previous researchers found that it can reduce anxiety and depression [66]. Referring to recent literature, another important factor that affects QoL is family sharing, which has not been evaluated [67]. Finally, the identification of permanent changes in psychological suffering might require a longer period of monitoring and assessment than 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a lack of attention to treatment information sharing between patients with ESKD and their family members, research in other illness populations has shown that patients who feel more able to share information about their illness with family members report better quality of life. 44 Additionally, both patients’ and care partners’ perceptions of the extent to which their family avoids talking about illness affects their own mental health and quality of life. 45 Therefore, ESKD treatment-related information sharing and communication within families may be a fruitful avenue for future research and intervention.…”
Section: Discussionmentioning
confidence: 99%